Perancangan Dan Pembuatan Sistem Pengolahan Data Pasien Pada Klinik Children And Adult Dental - Muhamad Vickry Almuhtadi Billah (Pusat riset dan Inovasi Nasional, 2023)
The dental clinic is a dental and oral health service for adults and children including children with autism and special needs. The concept of 'Children and Adult Dental Clinic' is to provide dental services in a friendly and comfortable manner for dental clinic patients and is efficient in data processing, therefore with the development of data processing systems, its application in dental clinics is also needed, the design and manufacture of patient data processing systems at dental clinics is not new in data processing systems, the application of dental clinic patient data processing systems is made based on the needs of the dental clinic 'Children and Adult Dental Clinic', whose data processing is still processed manually, this dental clinic patient data processing system application is made using SQL Server 2012 database, Visual Studio 2012 and Crystal Reports 2013, making this dental clinic patient data processing application is not easy, book sources are trusted and source from int ernet is a guide in making dental clinic patient data processing system applications, we hope this application can be applied and used as a computer-based data processing system in the dental clinic 'Children and Adult Dental Clinic'.